2016
DOI: 10.1186/s12889-016-3539-2
|View full text |Cite
|
Sign up to set email alerts
|

Intention of physicians to implement guidelines for screening and treatment of latent tuberculosis infection in HIV-infected patients in The Netherlands: a mixed-method design

Abstract: BackgoundAll newly diagnosed HIV-infected patients in the Netherlands should be screened for latent tuberculosis infection (LTBI) and offered preventive therapy if infected without evidence of active tuberculosis. This guideline, endorsed by the national professional body of HIV physicians is in line with international recommendations, and based on the increased risk of progression from LTBI to active tuberculosis in HIV-infected patients. The objective of the study is to assess the intention of HIV physicians… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
30
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(31 citation statements)
references
References 26 publications
(32 reference statements)
1
30
0
Order By: Relevance
“…In the present study, it was found that LTBI screening among PLWH was performed significantly more frequently in foreignborn individuals coming from high TB incidence countries. This is in agreement with what has been observed in other European countries, such as the Netherlands (Evenblij et al, 2016), Belgium (Wyndham-Thomas et al, 2016), and Switzerland (Elzi et al, 2007), as well as in non-European countries, such as Australia (Doyle et al, 2014). In contrast, a study performed in the United States demonstrated an association between the request for screening for LTBI diagnosis and poverty (Reaves et al, 2017).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…In the present study, it was found that LTBI screening among PLWH was performed significantly more frequently in foreignborn individuals coming from high TB incidence countries. This is in agreement with what has been observed in other European countries, such as the Netherlands (Evenblij et al, 2016), Belgium (Wyndham-Thomas et al, 2016), and Switzerland (Elzi et al, 2007), as well as in non-European countries, such as Australia (Doyle et al, 2014). In contrast, a study performed in the United States demonstrated an association between the request for screening for LTBI diagnosis and poverty (Reaves et al, 2017).…”
Section: Discussionsupporting
confidence: 91%
“…This is a very interesting issue; however this parameter was not evaluated in our survey. The low implementation of LTBI screening is likely due to the low perception of TB risk in PLWH (Evenblij et al, 2016), and to the awareness of the inaccuracy of LTBI tests, which can give falsenegative results in immunosuppressed persons (Goletti et al, 2014;Goletti et al, 2007;Vincenti et al, 2007) and are inadequate to predict progression to disease (Diel et al, 2011;Petruccioli et al, 2016a;Goletti et al, 2018a;Goletti et al, 2018b). The accuracy of LTBI tests improves if a selected population known to have a higher probability to progress to active disease is identified, as recommended in the recent guidelines of the British HIV Association (BHIVA) (BHIVA, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, engaging the community in TB detection has several challenges, including inadequate public knowledge regarding TB surveillance, insufficient ability to diagnose TB, limited geographical coverage, social economic barriers, low public awareness, and high stigma among healthcare workers and in communities (Ministry of Health Republic of Indonesia, 2018). In addition, a previous study pointed out that the barriers could be derived from internal factors of individual health workers; although individual health workers have received optimal education and training, their intention to perform TB case finding is not optimal (Evenblij, Verbon, & Van Leth, 2016). In supporting the duty of cadres to implement TB case finding, enhancing the intention of cadres to find TB cases at their community is important.…”
Section: Introductionmentioning
confidence: 99%
“…We acknowledge that physicians will be confronted with the challenge of assessing the patient-level risk and benefits while implementing these population-level public health activities [23,24]. Educational Selection of LTBI treatment regimen from the following treatment regimens based on an individual risk assessment: isoniazid alone (for 6-9 months) rifampicin alone (for 3-4 months) isoniazid and rifapentine (for 3 months) isoniazid and rifampicin (for 3-4 months) Programmatic issues Implementation of patient-centred strategies for service delivery Implementation of an integrated strategy including: material incentives and enablers counselling and education peer-based support culturally sensitive approaches…”
mentioning
confidence: 99%